Diving behaviour of Southern Right Whale in Golfo Nuevo, Peninsula Valdes, before starting feeding migration - Fernández, Santiago José; Coscarella, Mariano Alberto; Crespo, Enrique Alberto; Sucunza, Federico; Zerbini, Alexandre
Whales, at the end of the breeding season, can follow different strategies before they initiate their migration. However, their main objective is similar: finding food or mating. Southern right whales (Eubalaena australis) that reproduce in the Peninsula Valdés area are among the best studied whale populations. Information about the location of their migratory destinations and feeding grounds is increasing, but their diving behaviour is poorly understood. In this paper we analyse the diving patterns towards the end of the breeding season and the beginning of the migration using data from archival satellite tags within Golfo Nuevo. We used the dive shape manufacture’s classification of the dives: “Square” (associated with feeding activities), “V-Shape” (attributed to non-foraging dives as travelling) and “U-shaped” (attributed to feeding and search behaviours or social activity). Shallower and shorter dives were performed by mothers with calves as opposed to solitary individuals. A significant change in the proportion of the water column used during the Square shape dives developed by mother with calf, could be significate a change from coastal areas to deeper ones. Probably this change is seized by the mother to test if the calf is ready to start migration. This change occurs approximately four weeks before the mother calf pairs leave Golfo Nuevo. Fil: Fernández, Santiago José. Universidad Nacional de la Patagonia. Facultad de Ciencias Naturales. Sede Puerto Madryn; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Coscarella, Mariano Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro ...